2015
DOI: 10.1038/srep17538
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of Selected Tropical Plant Wastes Catalyzed by a Magnetic Carbonaceous Acid with Microwave

Abstract: In this study, magnetic carbonaceous acids were synthesized by pyrolysis of the homogeneous mixtures of glucose and magnetic Fe3O4 nanoparticles, and subsequent sulfonation. The synthesis conditions were optimized to obtain a catalyst with both high acid density (0.75 mmol g−1) and strong magnetism [magnetic saturation, Ms = 19.5 Am2 kg−1]. The screened catalyst (C-SO3H/Fe3O4) was used to hydrolyze ball-milled cellulose in a microwave reactor with total reducing sugar (TRS) yield of 25.3% under the best condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…Magnetic carbonaceous acid nanoparticles synthesized by pyrolysis from homogeneous mixtures of glucose and magnetic Fe 3 O 4 nanoparticles followed by sulfonation can potentially be used for the hydrolysis of plant wastes like bagasse, jatropha, and lukenetia hulls in microwave reactors. The results obtained suggested a significant level of hydrolysis and confirmed that acid‐functionalized nanoparticles can be used as promising catalysts for the pretreatment of various LBs.…”
Section: Nanotechnology For the Pretreatment Of Lbsupporting
confidence: 52%
“…Magnetic carbonaceous acid nanoparticles synthesized by pyrolysis from homogeneous mixtures of glucose and magnetic Fe 3 O 4 nanoparticles followed by sulfonation can potentially be used for the hydrolysis of plant wastes like bagasse, jatropha, and lukenetia hulls in microwave reactors. The results obtained suggested a significant level of hydrolysis and confirmed that acid‐functionalized nanoparticles can be used as promising catalysts for the pretreatment of various LBs.…”
Section: Nanotechnology For the Pretreatment Of Lbsupporting
confidence: 52%
“…Recent technologies using microwaves-, ultrasonication-and electricity-assisted approaches are also recommended to be explored in the field of nanotechnology. A study by Su et al [28] has demonstrated the potential of incorporating microwave-assisted technology with carbonaceous acid MNPs for the pretreatment and hydrolysis of sugarcane bagasse, Jatropha hulls and Plukenetia hulls. The hydrolysis performance obtained for sugarcane bagasse, Jatropha hulls and Plukenetia hulls was 58.3%, 35.6% and 35.8%, respectively.…”
Section: Lignocellulose For Conversion Of Cellulose To Biofuelmentioning
confidence: 99%
“…However, deciencies in these methods, such as the high cost of lipases, harsh deoxygenation conditions and incomplete separation of the catalyst particles from the products, remained and posed challenges to their further utilization in the large-scale production of biodiesel. [14][15][16][17][18] When catalyzing hydrolysis, esterication and dehydration reactions, solid acid catalysts, in particular sulfonated solid acid catalysts, exhibited excellent performance in the conversion of various alternative carbon resources, such as lignocellulosic biomass, 19 sugars, 20 and non-edible oils, 21,22 for the purposes of producing fuels and high-value-added chemicals. For example, sulfated mesoporous niobium oxide (MNO-S) was developed as a catalyst for the production of 5-hydroxymethylfurfural .…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic carbonaceous acids provided a convenient way of using a magnet for the isolation of catalysts. Novel carbonbased materials, including sulfonated magnetic lignin-derived amorphous carbon solid acids (MLC-SO 3 H), 24 magnetic carbon nanotube arrays (sulfonated MCNAs) 25 and magnetic carbonaceous acids, 19,26,27 were synthesized and successfully used in catalyzing the dehydration of fructose and the hydrolysis of polysaccharides and cellulose, respectively. However, these reported magnetic carbonaceous acids were not adequate for employment in the production of biodiesel with high efficiency owing to their relatively low acidity or magnetism (Table 1).…”
Section: Introductionmentioning
confidence: 99%